The low, low woods - Machado, Carmen Maria (DC Comics, 2020)
"When your memories are stolen, what would you give to remember? Follow El and Vee as they search for answers to the questions everyone else forgot. Shudder-to-Think, Pennsylvania, is plagued by a mysterious illness that eats away at the memories of those affected by it. El and Octavia are two best friends who find themselves the newest victims of this disease after waking up in a movie theater with no memory of the past few hours. As El and Vee dive deeper into the mystery behind their lost memories, they realize the stories of their town hold more dark truth than they could've imagined. It's up to El and Vee to keep their town from falling apart...to keep the world safe from Shudder-to-Think's monsters."--